2023
DOI: 10.1177/08971900231168927
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a Pharmacy-Driven Inpatient Chronic Obstructive Pulmonary Disease (COPD) Transitions of Care (TOC) Management Process

Abstract: Background Current data shows 30% of patients hospitalized for Chronic Obstructive Pulmonary Disease (COPD) exacerbation are readmitted within 30 days. Medication management during transitions of care (TOC) has shown impact on clinical outcomes, however there is insufficient data to suggest how pharmacy TOC services might benefit this patient population. Objective Evaluate the effects of pharmacy-driven COPD TOC services on hospital re-presentation rates. Methods A single-center retrospective chart review cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 12 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…This study highlights the high incidence of inappropriate inhaler prescribing in patients with COPD or asthma warranting hospitalization, as well as the impact of pharmacy team involvement on inhaler access and optimization in patients admitted to the hospital with COPD or asthma. The current study found a higher rate of inappropriate inhaler therapy in patients with COPD or asthma compared to Roberts and colleagues who recommended inhaler changes for approximately 30% of COPD patients prior to discharge ( n = 223) 14 . Results of this study are significant because maintenance inhaler therapy is essential to treating COPD and asthma and can significantly improve quality of life and reduce exacerbations that may lead to hospital admission and readmission 1,2 .…”
Section: Discussionmentioning
confidence: 42%
See 4 more Smart Citations
“…This study highlights the high incidence of inappropriate inhaler prescribing in patients with COPD or asthma warranting hospitalization, as well as the impact of pharmacy team involvement on inhaler access and optimization in patients admitted to the hospital with COPD or asthma. The current study found a higher rate of inappropriate inhaler therapy in patients with COPD or asthma compared to Roberts and colleagues who recommended inhaler changes for approximately 30% of COPD patients prior to discharge ( n = 223) 14 . Results of this study are significant because maintenance inhaler therapy is essential to treating COPD and asthma and can significantly improve quality of life and reduce exacerbations that may lead to hospital admission and readmission 1,2 .…”
Section: Discussionmentioning
confidence: 42%
“…Interventions included pharmacist-assessed clinical appropriateness as well as inhaler compatibility with insurance formulary restrictions. [11][12][13][14] Recently, a single-center retrospective chart review evaluating a pharmacy-driven COPD transitions of care service identified that up to 30% of admitted patients were recommended to have a change in inhaler therapy prior to discharge based on access barriers or current guidelines. 14 However, this study did not report the reasons for recommending an inhaler change, what medications were included, or what recommendations were made, and focused on admitted patients with COPD alone.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations